2002
DOI: 10.1034/j.1600-0854.2002.030405.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Delivery of Secretory Cargo in Golgi‐Derived Carriers of Nonepithelial Cells

Abstract: In epithelial cells, soluble cargo proteins destined for basolateral or apical secretion are packaged into distinct trans-Golgi network-derived transport carriers. Similar carriers, termed basolateral-and apical-like, have been observed in nonepithelial cells using ectopically expressed membrane marker proteins. Whether these cells are capable of selectively packaging secretory proteins into distinct carriers is still an open question. Here, we have addressed this issue by analyzing the packaging and transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…In previous studies on transfected CV-1 and Vero cells, the major localisation of CgA and CgB had been reported in the perinuclear GC/TGN area (Kim et al, 2001;Rustom et al, 2002). In addition, also discrete granin-positive puncta were reported to appear, however only in a fraction of the transfected cells.…”
Section: Expression Of Cga and Cgb In Non-secretory Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies on transfected CV-1 and Vero cells, the major localisation of CgA and CgB had been reported in the perinuclear GC/TGN area (Kim et al, 2001;Rustom et al, 2002). In addition, also discrete granin-positive puncta were reported to appear, however only in a fraction of the transfected cells.…”
Section: Expression Of Cga and Cgb In Non-secretory Cellsmentioning
confidence: 99%
“…In the case of CgA, and based on general ultrastructure, the corresponding organelles were defined as DCGs (Kim et al, 2001). With CgB, in contrast, the size of the organelles was large, and the DCG definition was proposed in one (Huh et al, 2003) but not in another (Rustom et al, 2002) case. In the present study the concentration of the two granins in the CG/TGN area was confirmed by co-labelling with specific markers, i.e.…”
Section: Expression Of Cga and Cgb In Non-secretory Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has pointed to the participation of vesiculotubular carriers in different cell secretory pathways. Well-documented examples are the transport system between the endoplasmic reticulum (ER) and Golgi complex [64][65][66][67], from the endosomal system [68] or the TGN [69,70] to the plasma membrane, and along axons [71][72]. These carriers appear as vesiculotubular structures of various shapes and sizes.…”
Section: Large Tubular Carriers Mediate Transport In Different Cell Smentioning
confidence: 99%
“…Curiously, such perturbation also inhibits secretory protein trafficking via the constitutive pathway (Wang et al, 2000), raising the hypothesis that certain lumenal proteins of the constitutive secretory pathway may also be selectively captured for entry into post-TGN transport intermediates (Rustom et al, 2002). In polarized MDCK epithelial cells where all newly synthesized secretory proteins transported to apical and basolateral media are thought to use constitutive secretion pathways, there is a precedent that at least some of these proteins may undergo selective capture by membranes of post-TGN transport intermediates (Caplan et al, 1987;Cheong et al, 1999;Kuhn et al, 2000;Martin-Belmonte et al, 2000;Martin-Belmonte et al, 2001;Urban et al, 1987;Zhang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%